How EHRs evolved from digital file cabinets to AI-ready systems. - Famakinwa, Joyce (Modern Healthcare, 2026)
The article focuses on the evolution and current state of electronic health records (EHRs) in healthcare, highlighting their transformation from basic digital file storage to interoperable systems that coordinate patient care. Major EHR companies—Epic Systems, Oracle Health, and Meditech—dominate 90% of the market, with government initiatives like the Health Information Technology for Economic and Clinical Health Act significantly accelerating adoption. Recent developments include the integration of artificial intelligence (AI) by leading vendors to enhance clinical support and administrative efficiency. Looking ahead, EHR providers aim to leverage data analytics and AI to enable predictive, coordinated, and proactive patient care.